Interconnected microgrids frequency response model: An inertia-based approach - S. Rehimi; R. Mirzaei; Hassan Bevrani (Energy Reports, 2020)
Preserving the frequency stability of new important blocks in smart grids such as interconnected microgrids, is a serious challenge. Inertia can act as a significant stability/performance index for frequency regulation in the power grids. Renewable energy sources have low inertia and mostly need a special control mechanism to emulate an inertia and inject to the system. In this work, a frequency response model is introduced for AC interconnected microgrids based on the inertia concept. The absence of a suitable model for study on frequency and tie-line power control in the interconnected microgrids, limits research activities in this field. A clear classification has not been done considering the inherent dynamic behavior of all distributed generators types, which may help researchers to introduce more simple strategies to provide better dynamic performance. This paper addresses a new approach for study on inertia-based simple frequency response model for interconnected microgrids. The outcome can be useful for frequency and tie-line power control analysis and synthesis in interconnected microgrids.
Keywords: 330; Frequency control; Frequency response model; Interconnected microgrids; Tie-line control; Virtual inertia